1996
DOI: 10.1164/ajrccm.153.1.8542141
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia in intubated trauma patients. Microbiology and outcomes.

Abstract: To describe the epidemiology of nosocomial pneumonia in trauma patients and its impact on outcome, we performed a retrospective case-control analysis. Quantitative bronchoscopic cultures were collected from 62 intubated patients with suspected pneumonia. Patients with proven pneumonia had higher abdominal injury scores. Those with bronchoscopy-negative pneumonitis were older. Age and injury severity were used to match two controls to each case. The incidence of pneumonia was 5.8% Streptococci and Hemophilus we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
110
1
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(124 citation statements)
references
References 32 publications
8
110
1
5
Order By: Relevance
“…24 In unselected populations of mixed ICU patients, an incidence of early-onset pneumonia between 5% and 25% has usually been reported. [25][26][27][28][29] Our rate of 15.5% among liver recipients agrees with previously reported rates of pneumonia after LT ranging from 5% to 34%. [4][5][6][7][8][9][10]30 Two recent studies showed a rate of pneumonia of 21.1% in liver recipients receiving a 3-day prophylactic regimen of CTX and ampicillin and a rate of 18% in living donor-related recipients receiving selective digestive decontamination.…”
Section: Discussionsupporting
confidence: 92%
“…24 In unselected populations of mixed ICU patients, an incidence of early-onset pneumonia between 5% and 25% has usually been reported. [25][26][27][28][29] Our rate of 15.5% among liver recipients agrees with previously reported rates of pneumonia after LT ranging from 5% to 34%. [4][5][6][7][8][9][10]30 Two recent studies showed a rate of pneumonia of 21.1% in liver recipients receiving a 3-day prophylactic regimen of CTX and ampicillin and a rate of 18% in living donor-related recipients receiving selective digestive decontamination.…”
Section: Discussionsupporting
confidence: 92%
“…Between 250,000 and 300,000 cases per year occur in the United States alone, which is an incidence rate of 5 to 10 cases per 1,000 hospital admissions (134,170). The mortality attributable to VAP has been reported to range between 0 and 50% (10,41,43,96,161). Studies have provided different results when determining attributable mortality, in part because of very different populations (less-acute trauma patients, acute respiratory distress syndrome [ARDS] patients, and medical and surgical ICU patients) and in part as a result of variances in appropriate empirical medical therapy during the initial 2 days.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in the understanding of the epidemiology of VAP, some fundamental aspects, such as its influence on in-ICU mortality and time in ICU, remain a matter of controversy, and conflicting data have been observed in the literature. (5)(6)(7)(8) The present study, through the prospective follow-up of patients submitted to MV in the ICU of a private hospital in the city of Rio de Janeiro, Brazil, can be included in this context. Comparing the subgroup of patients who developed VAP with the remaining patients, we sought to determine the impact of VAP on the prognosis of the patients submitted to MV by assessing the following primary outcomes: in-ICU mortality rate; time on MV; time in ICU; and overall length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%